Intensi Penggunaan Kembali Pinjaman Online: Tinjauan atas Kemudahan Aksesibilitas, Pengalaman Penggunaan, dan Kelompok Acuan - Rahayu Mardikaningsih; Marta Jauzanajla Deliasari Fernanda (Universitas Respati Indonesia, 2026)
This literature study aims to analyze the role of accessibility within the Technology Acceptance Model framework, user experience as perceived benefit, and reference groups as social referents in shaping the repurchase intention of online loans. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that accessibility serves as a gateway enabling initial adoption through simple, fast, and hassle-free processes. User experience after trying the service shapes perceived benefit, determining whether users feel the service provides added value as expected. Reference groups, both through direct interaction and electronic word of mouth, provide social validation that strengthens or weakens the decision to reuse. These three factors interact dynamically, where accessibility opens opportunities, positive experience builds trust, and reference group support provides social legitimacy. Users who experience ease, obtain real benefits, and receive reinforcement from their social environment develop loyalty reflected in high repurchase intention. This study contributes theoretically to enriching technology adoption literature by integrating personal experience and social influence dimensions, and practically provides reflective foundations for online loan providers in designing user-centered services, for marketers in developing community-based strategies, and for regulators in creating consumer protection ecosystems.